Immunoregulatory functions of natural killer cells in avian influenza virus infection - P. O. Shatunova; M. V. Gavrilova; A. A. Rtishchev; T. A. Kolyganova; T. A. Zaytseva; S. G. Markushin (Медицинская иммунология, 2023)
The avian influenza virus (AIV) has a great pandemic potential both in animals, and in human population. For effective struggle against this virus, it is important to study the immune response against AIV, and, in particular, the features of T cell immunity. At the period of early immune response, when the activation of adaptive immunity factors has not yet occurred, the natural killers, which have both cytotoxic and immunoregulatory functions, are known to play a key role in the fight against the influenza virus. In this study, we investigated the interaction between natural killers and T helpers in the process of antiviral response. The aim of this study was to study immunoregulatory functions of NK cells in BALB/c mice vaccinated with different doses of avian influenza virus.We used a strain of mouse-adapted avian influenza virus (AIV) of the H5N2 serotype (A/duck/ Pennsylvania/10218/1984). The determination of the virus titer in the mice lung tissue was performed by infecting 10-day-old chicken embryos (SPF) with lung extracts at various decimal dilutions, followed by the immune agglutination test. Quantitative determination of natural killers and T helpers (Th) in the mice spleen tissue was carried out by flow cytometry. The amount of Th cells in mice spleens increased at low infectious dose (2.5 EID50) which is explained by active clonal expansion of this cell subpopulation. The infectious disease process ended upon complete virus elimination from the lungs. The amounts of Th cells were also increased in a group of mice infected with intermediate infectious dose (25 EID50), however, being accompanied by virus replication in lungs. When the mice were infected with a high dose of the virus (250 EID50), there was a decrease in the Th cells number versus control group of animals, whereas replication of AIV was noted throughout the entire observation period in the lung tissue.The amounts of helper T cells at high doses of viral infection could be decreased due to activation of NK cells. The activated NK cells may then eliminate exhausted helper T cells. Thus, NK cells immunoregulatory function represents an important immunological factor which keeps balance between the pathogen destruction and excessive inflammation of the lung tissue affected by the avian influenza virus.